The concept and the realization of the high-power laser diodes with multi-stripe-gain distribution - Sobczak, Grzegorz Tadeusz; Dąbrowska, Elżbieta; Teodorczyk, Marian; Krzyżak, Konrad; Kalbarczyk, Joanna; Maląg, Andrzej (Photonics Letters of Poland, 2013)
The slow axis far-field widening (far-field blooming) is one of the factors, which decrease the quality of the emitted beam of high-power laser diodes. This effect is connected with rising number of maintained lateral optical modes in the laser waveguide. In this paper the design of the gain distribution by the steering of current flow is presented as a way to restrict the far-field blooming. The numerical and experimental results are presented. The almost constant slow-axis width of the optical field distribution in the far-field is obtained up to four times above the threshold current. Full Text: PDF References J. Piprek, "Inverse Thermal Lens Effects on the Far-Field Blooming of Broad Area Laser Diodes", IEEE Photon. Technol. Lett., 25, 958 (2013) CrossRef J. Piprek, "Self-consistent far-field blooming analysis for high-power Fabry-Perot laser diodes", Proc. SPIE 8619, 861910 (2013) CrossRef P. Crump, S. Boeldicke, C. M. Schultz, H. Ekhteraei, H. Wenzel and G. Erbert, "Experimental and theoretical analysis of the dominant lateral waveguiding mechanism in 975 nm high power broad area diode lasers", Semicond. Sci. Technol., 27, 045001 (2012) CrossRef Y. Twu, K. L. Chen, A. Dienes, S. Wang and J. R. Whinnery, "High-performance index-guided phase-locked semiconductor laser arrays", Electron. Lett., 21, 324 (1985) CrossRef M. V. Maximov, Y. M. Shernyakov, I. I. Novikov, L. Ya. Karachinsky, N. Yu. Gordeev, U. Ben-Ami, D. Bortman-Abriv, A. Sharon, V. A. Shchukin, N. N. Ledentsov, T. Kettler, K. Posilovic, D. Bimberg, "High-Power Low-Beam Divergence Edge-Emitting Semiconductor Lasers with 1- and 2-D Photonic Bandgap Crystal Waveguide", IEEE J. Sel. Topics Quantum Electron., 14, 1113 (2008) CrossRef G. Sobczak, E. Dąbrowska, M. Teodorczyk, J. Kalbarczyk and A. Maląg, "Characterization of the optical beam emitted by high-power phase-locked arrays of diode lasers (P = 1 W CW)", Proc. SPIE 8902, 890217 (2013) CrossRef G. Sobczak, A. Maląg, "Optimization of phase-locked arrays geometry for high brightness laser systems", Opto-Electronics Review, 20, 134 (2012) CrossRef G. Sobczak, E. Dąbrowska, M. Teodorczyk, J. Kalbarczyk and A. Maląg, "Improving the beam quality of high-power laser diodes by introducing lateral periodicity into waveguides", Proc. SPIE 8702, 87020B (2013) CrossRef M. Spreemann, B. Eppich, F. Schnieder, H. Wenzel and G. Erbert, "Modal Behavior, Spatial Coherence, and Beam Quality of a High-Power Gain-Guided Laser Array", IEEE J. Quantum Electron., 46, 1619 (2010) CrossRef A. Maląg, E. Dąbrowska, M. Teodorczyk, G. Sobczak, A. Kozłowska and J. Kalbarczyk, "Asymmetric Heterostructure With Reduced Distance From Active Region to Heatsink for 810-nm Range High-Power Laser Diodes", IEEE J. Quantum Electron., 48, 465 (2012) CrossRef A. Kozłowska, A. Maląg, "Far-field emission characteristics of high-power laser diodes", Proc. SPIE 5120, 183 (2003) CrossRef W. Sun, R. Pathak, G. Campbell, H. Eppich, J. H. Jacob, A. Chin and J. Fryer, "Higher brightness laser diodes with smaller slow axis divergence", Proc. SPIE 8605, 86050D-1 (2013) CrossRef